Krishna as the archetypal guru: A theoretical framework of divine pedagogy in the Bhagavad Gita - Sapkota, Hari Prasad (Indonesian Journal of Education and Pedagogy, 2025)
This theoretical article explores the pedagogical qualities of Lord Krishna, considering his role as the ideal guru in Hinduism and his practice within the holistic approach to transformational pedagogy in contemporary educational institutions. Despite extensive study, a gap remains in systematically applying Krishna’s classical pedagogical principles to modern classrooms, including holistic teaching, crisis-responsive strategies, and transformational learning approaches. It employs qualitative analysis focused primarily on the Bhagavad Gita to analyze the higher-order pedagogical processes through which Krishna taught, the guru-disciple relationship, and its profound transformative impact on student development. This study explores Lord Krishna’s exemplary pedagogy, emphasizing individualized diagnostic assessment and adaptive multi-modal communication as foundational strategies. Further, Krishna’s crisis-responsive teaching and systematic consciousness transformation demonstrate adaptive and transformational excellence, fostering ethical empowerment. These principles transcend cultural boundaries and hold practical implications for modern education, leadership development, and therapeutic practice, offering a holistic framework that bridges classical wisdom and contemporary educational challenges. Additionally, the study highlights the importance of intercultural dialogue, moral resilience, and social-emotional and holistic growth on a global scale.  Future research is recommended to empirically validate these frameworks and develop assessment tools and training programs, integrating Krishna’s pedagogical principles with contemporary educational and leadership practices.